Is basic level game-based approach suitable for accounting students with previous accounting knowledge? / Humairaa Hasan … [et al.] - Hasan, Humairaa; Hamzah, Nurul Hassanah; Suhaimin, Suliza; Ahmad, Mohamad Azmi Nias; Mohd Din, Norlaila; Jamaluddin, Junaidah; Mohammad Fadzillah, Nur Syazwani; Abdul Jabar, Faizan (Universiti Teknologi MARA, Pahang, 2022)
The three important components of a company’s Statement of Financial Position are the assets, owner’s equity and liabilities. The accounting equation depicts the interrelationships between these three components and aids in determining if a company’s business operations are accurately reflected in its books of accounts. From the accounting education’s point of view, students should master this fundamental concept in preparing financial statements, yet for most students, accounting can be a challenging subject. Students should not only show their competency in knowing the accounting process, but also a comprehensiveness of knowledge and understanding of the accounting concepts and fundamentals. Accounting is traditionally taught by textbooks-based lectures with all the workings being illustrated on the blackboard or whiteboard, while the students passively listen or jot down notes. Some says that this is the most effective way to learn accounting whereas others prefer teaching tools to help them improve the students’ views of learning, exam performance and the learning curve. To feel certain of whether the differentiated learning methods would affect the student’s understanding and performance, a study is conducted to shed some light in this area. A survey method is used, focusing on samples which are obtained from 69 closely selected diploma accounting students, with previous accounting knowledge. The results have disclosed that with the presence of their previous accounting knowledge, both traditional and game-based learning methods are suitable for accounting students.